DEVELOPMENT OF ENGLISH LEARNING MATERIALS IN GENRE BASED ON GAYO LOCAL CULTURE - Khoiriyah Shofiyah Tanjung; yulizar - - (ETERNAL (English, Teaching, Learning and Research Journal), 2019)
In several schools in Central Aceh, students’ average in writing is about 71 from the minimum score 70, it means that the students are still weak in writing. One of the problem is students are unfamiliar with topic in writing genre. This study aims to improve students’ skill in writing by developing the English teaching material in genre based on Gayo local culture. Before developing the material, the writers observed some schools in Central Aceh about students’ problem in writing English. After getting the data abaout students’ problem, the writers designed the teaching material in genre based on Gayo Local culture. The next step is modifying the teaching material and it should be validated by some expert. The valid design then disseminate to some Madrasah Aliyah in central Aceh. All the stage in this research namely 4D stage. Data collected in this study is Lesson Plan and Material development validation sheet. The result of this study is a handbook of text types (genre) based on Gayo local culture. Developed teaching materials are expected to improve students’ writing ability.